Theoretical and experimental study of the electronic, crystalline, morphologic, compositional, magnetic and dielectric properties of the Sr2DyNbO6 material (2017)
We report experimental and theoretical results of crystal structure, morphology, magnetic and electric features, and electronic structure for the Sr2DyNbO6 ceramic compound. Samples were produced by the solid-state reaction recipe. X-ray diffraction experiments show that the material crystallizes in a monoclinic structure, P21/n space group. SEM images exhibit a granular submicrometric surface. Temperature curves of magnetic susceptibility reveal a paramagnetic response. Curie law fitting permitted to obtain a magnetic moment 10.28 μB. Polarization as a function of electric fields shows a hysteretic feature with 264.28 relative dielectric constant at 300 K. DFT calculations of electronic structure suggest the semiconductor character of this material, energy gap 3.21 eV for the spin-up polarization and 0.26 eV for spin-down. The calculated effective magnetic moment was 10.0 μB, which is strongly in accordance with the measured value. The theoretical cell parameters obtained from the Murnaghan state-equation are 98.5% in agreement with the experimental result.